The Development of Liveworksheets-Based E-Worksheet for Plane Shapes Learning in Fourth Grade Elementary School - Fitry Fakhirah Azzahra; Aulia Rahma Syadila; Fitri Nur Ramdaniyah; Yuni Nurfauziah; Asep Nuryadin (Journal on Education, 2024)
Ideal learning involves effective interaction among all learning components. This paper delineates the stages of developing a Liveworksheets-based Electronic Worksheet (E-Worksheet) on plane shapes, aiming for creative and diverse learning experiences in the classroom, fostering greater interactivity. The study adopts the Research and Development (R&D) method or design research. It adheres to the ADDIE development model (Analysis, Design, Develop, Implement, Evaluate) encompassing five research stages. The development process yielded data showing expert validation results, with media expert validation at 96.4% categorized as "Highly Valid," and content expert validation at 95% categorized as "Highly Valid." Meanwhile, practicality assessments from student questionnaires resulted in 98.76%, categorized as "Highly Practical." It can be inferred that the Liveworksheets-based E-Worksheet developed by the researcher is valid and practical. This aspect not only enhances interactivity in learning but also ensures ease of use.